2011
DOI: 10.1111/j.1468-5906.2011.01598.x
|View full text |Cite
|
Sign up to set email alerts
|

Orthodoxy Niches: Diversity in Congregational Orthodoxy Among Three Protestant Denominations in the United States

Abstract: The organizational niche, a fruitful concept from the organizational ecology literature, frames this study on the diverse orthodoxy of congregations within the same denomination. Congregations diversify along a conservativeto-liberal continuum, which lessens niche overlap with nearby congregations in their denomination. Pastors and priests in United Methodist and Episcopal congregations in three U.S. regions were able to locate their congregations (and other congregations in their denomination in close proximi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Thus to the extent that religion influences work by exposing adherents to relevant teachings, there is little reason to expect consistent effects of attendance. Second, congregations, even within the same denomination, differ markedly in levels of orthodoxy (Reimer 2011;Wuthnow 1988). To the extent that religion shapes work orientations through orthodoxy, we would expect the effects of attendance to wash out due to congregational and denominational heterogeneity.…”
Section: Beyond Orthodoxymentioning
confidence: 99%
“…Thus to the extent that religion influences work by exposing adherents to relevant teachings, there is little reason to expect consistent effects of attendance. Second, congregations, even within the same denomination, differ markedly in levels of orthodoxy (Reimer 2011;Wuthnow 1988). To the extent that religion shapes work orientations through orthodoxy, we would expect the effects of attendance to wash out due to congregational and denominational heterogeneity.…”
Section: Beyond Orthodoxymentioning
confidence: 99%
“…A comprehensive literature review is neither necessary nor desirable here, but even a cursory look at recent literature makes clear that congregations continue to be studied from many perspectives to learn about many subjects. Looking just at work published since 2010, research on congregations has focused on race and ethnicity (Edwards, Christerson, and Emerson ; Marti ), small groups (Dougherty and Whitehead ), civic and political participation (Schwadel ), leadership (Edwards ; Stewart‐Thomas ), openness to gays and lesbians (Adler ; Whitehead ), HIV/AIDS services (Derose et al ; Frenk and Trinitapoli ; Fulton ), environmentalism (Djupe and Olson ), organizational identity (Reimer ), organizational networks (Smith, Schietle, and Bader ), worship styles (Baker ), principal‐agent problems (Wollschleger ), change over time (Chaves ; Roozen ), and much more.…”
Section: Introductionmentioning
confidence: 99%
“…The secular or religious identification of the member institutions, the value placed on research, and the use of religious authorities distinguish religious from secular workplace spirituality networks, despite their common interests and scholarly sources. Reimer (2011) suggested that more conservative Christian denominations demonstrate narrower doctrinal allowances among congregations associated with a particular denomination. Conservative religious colleges serve in part as moral communities, assuming religion to be rational and vital to the institution's mission, and accepting scriptural and theological authority (cf.…”
Section: Discussionmentioning
confidence: 98%